Effect Of Aggregated And Distributed Approach In precision of implementation some of the Basic skill for Football of age 13 Years - Galil, Qahtan; Radi, Saleh (Journal of Physical Education, 2008)
includes definition, problem, aims, and hypotheses; the basic aim was to arrive at proper performance in a shorter time. This is done by programming and organizing work and rest periods between every two repetitions and between groups of refutations. This is intended to guarantee balance between number of repetitions in the learning unit and the amount of learning achieved to get the optimum skill standard in as short time as possible. Aims of the study: knowing the effect of aggregated and distributed approach the basic football skills. Hypotheses: There are statistically abstract differences influencing the learning of the basic skills by the two approaches (aggregated and distributed). Chapter two: it includes the theoretical. Chapter Three: it includes the program and field procedures. The research used the experimental program on (20) player of school football. We also made a pilot experiment to define the rest period between every repetition and every group of repetitions. We, then, carried the test and measurements for the conformity of the two group's members, then applying the training program, and the evaluation of the skills under study, chapter four: It presents, analyzes and discusses the results. The research did all this scientifically based on recommendations, which can be summed up as follows: Chapter five: Results revealed that there were statistically abstract differences between the pre and post – tested for the two approaches and favor of the post-tests for all skills. The best using the style massed practice in learning skills, gosling and passing. And the best using the style distribute practice in learning skill, head passing.